On a Certain Theory of Plasticity Solutions for the Heavy Machine Earth-Working Process - Jarzębowski, A.; Szyba, D.; Trąmpczyński, W. (Engineering Transactions, 1994)
The aim of this paper is to apply kinematic solutions of the theory of plasticity for description of a soil shoving process for such heavy machine tools as buckets of the loading machines, excavators etc. Assuming the material to be rigid-plastic with softening, which obeys the Coulomb – Mohr yield criterion and the associated flow rule, kinematic solutions for the initial and subsequent phases of the process were found. Characteristic rigid zones, which are periodically generated during the cohesive soil cutting process, and periodicity of the resulting force were predicted in this way. Theo, theoretical results were compared with experimental data showing good agreement with theoretical prediction.